Public Services: A Satisfaction Survey of Dumai City Hospital Services - Dedy Afrizal; Dila Erlianti; E-Maznah Hijeriah; Lis Hafrida; E. Erinaldi; S. Sofyan (Manunggal Halim Jaya, 2024)
Public service is a frequently discussed issue in Indonesia. However, when it comes to execution, local governments as service providers must consider a variety of factors. Regarding the government-owned regional hospital services that have been operating. One of them is monitoring the public satisfaction index for the services provided by Dumai city hospital. With the expectation that the findings may help policymakers at the regional hospital enhance future services. This article is intended to assess public satisfaction with the services offered by Dumai city hospital. The study used a quantitative technique measuring the Community Satisfaction Index established by the Regulation of the minister of state apparatus empowerment and bureaucratic reform of the republic of Indonesia number 14 of 2017 concerning guidelines for compiling public satisfaction surveys of public service provider units. There are nine items that are measured: requirement, systems mechanisms and procedures, time to completion, fees/rates, product specification type of service, officer behavior, competence of service officers, handling, complaints, suggestions and input, facilities and infrastructure. The study's population represents the entire community that has received services. The sample size was determined using the accidental sampling technique with 100 respondents. A questionnaire has been used for collecting the data required. The research study found that the community satisfaction index was 80.75, and the assessment category service satisfaction was good.